Rapid Loss of RNA Detection by In Situ Hybridization in Stored Tissue Blocks and Preservation by Cold Storage of Unstained Slides. Issue 5 (9th October 2017) - Baena-Del Valle, Javier A; Zheng, Qizhi; Hicks, Jessica L; Fedor, Helen; Trock, Bruce J; Morrissey, Colm; Corey, Eva; Cornish, Toby C; Sfanos, Karen S; De Marzo, Angelo M
Abstract: Objectives: Recent commercialization of methods for in situ hybridization using Z-pair probe/branched DNA amplification has led to increasing adoption of this technology for interrogating RNA expression in formalin-fixed, paraffin-embedded (FFPE) tissues. Current practice for FFPE block storage is to maintain them at room temperature, often for many years. Methods: To examine the effects of block storage time on FFPE tissues using a number of RNA in situ probes with the Advanced Cellular Diagnostic's RNAscope assay. Results: We report marked reductions in signals after 5 years and significant reductions often after 1 year. Furthermore, storing unstained slides cut from recent cases (<1 year old) at –20°C can preserve hybridization signals significantly better than storing the blocks at room temperature and cutting the slides fresh when needed. Conclusions: We submit that the standard practice of storing FFPE tissue blocks at room temperature should be reevaluated to better preserve RNA for in situ hybridization.